Group Emotional Contagion and Complaint Intentions in Group Service Failure: The Role of Group Size and Group Familiarity. (August 2014) - Du, Jiangang; Fan, Xiucheng; Feng, Tianjun
Service failure is well documented in service marketing literature, which mainly focuses on service interactions between employees and individual customers. However, prior research has not examined customers' emotional and behavioral responses during group service failure—that is, a service involving a group of customers who do not meet the expectations of all or the majority of the customers. Compared with service failure involving individual customers (individual service failure), customers in group service failure are likely to show different emotional and behavioral characteristics. The authors conduct two experiments and find that customers have higher levels of anger and complaint intentions in group service failure than in individual service failure. In addition, the displays of anger by surrounding customers are positively related to individual customers' anger. Through a second experiment, this article further investigates the role of group size and group familiarity on group emotional contagion during group service failure. The results show that both group size and group familiarity moderate the relationship between the displays of anger by surrounding customers and an individual customer's anger—that is, the effect of group emotional contagion is stronger in a large/familiar group than in a small/unfamiliar group. The results provide several theoretical and managerial implications for research in group service failure.